Network pharmacology and molecular docking to elucidate the mechanism of pulsatilla decoction in the treatment of colon cancer - Liu, Huan; Hu, Yuting; Qi, Baoyu; Yan, Chengqiu; Wang, Lin; Zhang, Yiwen; Chen, Liang (Frontiers in Pharmacology, 2022)
Objective: Colon cancer is a malignant neoplastic disease that seriously endangers the health of patients. Pulsatilla decoction (PD) has some therapeutic effects on colon cancer. This study is based on the analytical methods of network pharmacology and molecular docking to study the mechanism of PD in the treatment of colon cancer. Methods: Based on the Traditional Chinese Medicine Systems Pharmacology Database (TCMSP), the main targets and active ingredients in PD were filtered, and then the colon cancer-related targets were screened by Genecards, OMIM, PharmGKB, and Drugbank databases. Then the screened drug and disease targets were Venn analyzed to obtain the intersection targets. Cytoscape software was used to construct the "Components-Targets-Pathway" map, and the String database was used to analyze the protein interaction network of the intersecting targets and screen the core targets, and then the core targets were analyzed by Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis. Molecular docking was implemented using AutoDockTools to predict the binding capacity for the core targets and the active components in PD. Results: Sixty-five ingredients containing 188 non-repetitive targets were screened and 180 potential targets of PD anti-colon cancer were identified, including 10 core targets, namely MAPK1, JUN, AKT1, TP53, TNF, RELA, MAPK14, CXCL8, ESR1, FOS. The results of Go analysis showed that the PD anti-colon cancer may be related to cell proliferation, apoptosis, energy metabolism, immune regulation, signal transduction, and other biological processes. The results of KEGG analysis indicated that the PI3K-Akt signaling pathway, MAPK signaling pathway, Proteoglycans in cancer, IL-17 signaling pathway, Cellular senescence, and TNF signaling pathway were mainly involved in the regulation of tumor cells. We further selected core targets with high degree values as receptor proteins for molecular docking with the main active ingredients of the drug, including MAPK1, JUN, and AKT1. The docking results showed good affinity, especially quercetin. Conclusion: This study preliminarily verified that PD may exert its effect on the treatment of colon cancer through multi-ingredients, multi-targets, and multi-pathways. This will deepen our understanding of the potential mechanisms of PD anti-colon cancer and establish a foundation for further basic experimental research.